Lamb Head as a Training Model for Septoplasty and Rhinoplasty - Apaydin, Fazil; Saghir, Meshari; Garcia, Rodrigo Fortunato Fernandez Pellon; Daoud, Mahmoud; Jaber, Ayman (Facial Plastic Surgery, 2022)
Septoplasty and rhinoplasty are difficult operations to learn and teach. Many modalities have been proposed to make the teaching process of these operations easier. In this study, it was investigated if lamb heads were good training models to teach septoplasty and rhinoplasty to trainees or experienced surgeons. In the first part of the study, 21 lamb heads were dissected according to a dissection protocol and several anatomical distances were measured to compare them with human cadavers. In the second part, eight lamb heads were dissected and different preservation rhinoplasty techniques were practiced. The study on 21 lamb heads used showed that the lateral crura were 17.8 × 11.6, the average interdomal distance was 8.1 mm, and the average domal width was 3.7 mm. The average length of the upper lateral cartilages was 31.1 mm laterally and 21.2 medially. The average length of the nasal bones was 63.9 mm, and the width was 16 mm. In the second part of the study, 8 lamb heads were used to experience where high-strip techniques were used in 5 and the Cottle technique in 3. This study revealed that lamb heads should be considered as an excellent training model for septoplasty and rhinoplasty. Its very low cost, ease of availability, and close similarity to the human cadavers can be counted as the main advantages. This study also proved that it was not only a tool for beginners, but also a very helpful tool for experienced surgeons to try new methods.
Keywords: rhinoplasty; septoplasty; rhinoplasty training; animal models; lamb heads